Doubling farmers’ income: Its necessity and possibilities in Indian context - Roy, Pinaki; Bhattacharyya, Sangeeta (The Indian Journal of Agricultural Sciences, 2020)
At the crucial juncture of Indian economy trying hard to shoot up its way to the trillion dollar economy club, it is inevitable that agricultural sector needs to contribute a large part to it, considering the fact that India is an agrarian economy. But this dream is impossible without thinking of a way out to increase farmers’ income because ultimately the responsibility of food security of our nation rests on their shoulders and if they are feeble, then we can never expect any dream of economical growth to come true. With farmer suicide rate being 9.4 per cent and per capita income of farmer staggering low each year, it is difficult but not impossible to increase farmers’ income. The article is a discussion of what models can be followed to achieve to some extent if not possible to fulfill the Prime Minister’s call of Doubling Farmers’ Income by 2022. The authors elaborate on the CPRV Model and the points of intervention from farm to fork pathway of any agricultural produce.